Reproductive efficiency and milk yield in Sindhi breed cattle - Rafaella da Rocha Olivieri de Barros; Raquel Rodrigues Costa Mello; Sabrina Luzia Gregio de Sousa; Kaliane Nascimento de Oliveira; Jorge Carlos Dias de Sousa; Elisa Cristina Modesto; Marco Roberto Bourg de Mello (Brazilian Journal of Veterinary Medicine, 2022)
The aim of this study was to identify the average of productive and reproductive traits in Red Sindhi females and evaluate if there is an influence of the reproductive traits on milk yield in this breed. Data related to reproductive and productive traits of 638 Sindhi breed dairy cows from North, Northeast, Midwest and Southeast regions of Brazil were provided by ABCZ. Analysis of variance followed by analysis of correlation among reproductive traits and between these and milk yield traits were used. Averages for age at first calving (AFC), calving age (CA), calving interval (CI), reproductive efficiency (RE), dry period (DP), lactation period (LP),milk yield (MY), and total milk yield (TMY) were 549.83 ± 560.47 days; 1843.53 ± 739.99 days; 533.28 ± 206.66 days; 75.46 ± 19.95%; 248.28 ± 206.66 days; 263.22 ± 63.51 days; 7.08 ± 2.78 kg of milk. day-1 and 1875.28 ± 893.36 kg of milk.lactation-1, respectively. The traits AFC, calving order (CO), CA, CI, RE and LP were separated into categories and there was no effect on MY among different categories, while the CO showed positive correlation with LP. Therefore, it can be concluded that Red Sindhi breed dairy cows showed high averages for AFC and medium averages for MY, CI and RE.